Cardiovascular Diseases As Risk Factors Of Post-Covid Syndrome: A Systematic Review - Nur Insyirah Sha’ari; Aniza Ismail; Aznida Firzah Abdul Aziz; Leny Suzana Suddin; Amirah Azzeri; Ruhana Sk Abd Razak; Nur Syazana Mad Tahir (BioMed Central Ltd, 2024)
Indexed by WOS/Scopus/ERA